Hêlēl ben-Šaḥar and the Chthonic Sun: A New Suggestion for the Mythological Background of Isa 14:12-15 - Quick, L (Brill, 2018)
This paper will explore the oft investigated problem of the mythological referents which inform Isa 14:12-15. Crucial to this will be a reinterpretation of the mysterious hêlēl ben-šaḥar of v. 12, almost universally understood by commentators and translators alike to refer to the ‘Day Star, son of the Dawn’, and thus taken to refer to the ‘morning star’, the planet Venus. Much of the scholarship has approached the ancient Near Eastern material with this meaning in mind, yet no myth hitherto proposed has provided a complete analogy to Isa 14:12-15. Thus I will begin by exploring the problems with these previous analogies, before reconsidering the meaning of hêlēl ben-šaḥar . Understanding the phrase to metonymically remind of the sun itself, the Ugaritic conception of the chthonic sun will be proposed to provide a much more satisfying parallel with our Isaiah passage.